Methods of potassium contents evaluation in the substrate solution and gerbera leaves - Ludwig, Fernanda; Fernandes, Dirceu Maximino [UNESP]; Guerrero, Amaralina Celoto; Ferreira, Guilherme Amaral; Pohlmann, Valeria (FapUNIFESP (SciELO), 2019)
Several authors report that potassium (K) is the nutrient absorbed in greater amounts by gerbera plants. Thus, objective of determining the concentration of Kin the solution of substrates for growing potted gerbera, quantified by the Cardy Horiba C-131 and an atomic absorption spectrophotometer, correlating them with each other and with the plant leaf content. The experiment was carried out in a greenhouse. The experimental design was in randomized complete blocks usinga 5x2 factorial scheme (5 substrates/2 cultivars) and four replications. Cherry and Red gerbera cultivar seedlings with four final leaves were transplanted into pots, filled with the substrates and acclimated for 30 days. After acclimation,the K content in the substrate solution extracted by the PourThru methodology was evaluated every two weeks using the Cardy Horiba C-131 portable ion meter and an atomic absorption spectrophotometer, as well as the K content in the leaves of gerbera plants. The solution of the commercial substrate had higher concentrations of K in relation to theothers in the two forms of measurement, which is directly related to the high initial contents of the nutrient in this substrate. This is directly related to the high initial K contents in the substrate. Greater values of K were obtained for the cultivar Red, both in the solution and in the leaves. The K concentration of the substrate solution cultured with gerbera plants quantified by the Cardy Horiba C-131 and atomic absorption spectrophotometry correlated significantly with each other and showed a low correlation with the content of this nutrient in the plant tissue.
Keywords: Fertilization; Gerbera jamesonii; Plant nutritino